The influence of digital transformation on the supply chain finance level - Liu, Zongtuan; Zhang, Jiajie; Cao, Lei; Xu, Ying (Frontiers in Physics, 2025)
In the new era, supply chain finance (SCF), as an emerging financial model, has gradually become an important means for enterprises to develop and improve supply chain efficiency. The continuous development and application of digital technology have brought unprecedented opportunities and challenges for the digital transformation of SCF. This article is based on the data of non-financial industry listed companies in China’s Shanghai and Shenzhen A-shares from 2007 to 2021. It examines the relationship between digital transformation and enterprise SCF. Research has found that the degree of digital transformation and SCF level of enterprises are constantly increasing. The digital transformation of enterprises is conducive to improving their SCF levels and to further exploring the impact of various dimensions of digital transformation on SCF levels. This promoting effect still exists. This study aims to provide a profound and practical theoretical basis for digitizing the SCF level, thereby highlighting the importance and value of SCF in the modern economy.